The effect of childhood trauma on moral cognition in patients with schizophrenia - Peng, Xing; Ding, Yu-shen; Ren, Bo; Zhao, Xi-xi; Wang, Fei-fei; Zhao, Jie; Zhang, Yuan-yuan; Zhang, Xiu-jun; Zhou, Fu-chun; Wang, Chuan-yue (Frontiers in Psychiatry, 2024)
The aim of this study was to investigate whether a potential moral cognitive impairment (failure in understanding moral rules) exists in schizophrenia(SCZ) and to explore the effect of childhood trauma (CT) on moral cognition in SCZ. Methods: A total of 99 SCZ and 102 healthy controls (HCs) were included in this study. The Childhood Trauma Questionnaire-Short Form (CTQ) was administered to assess childhood trauma experiences in both groups, while the Moral Identity Measure (MIM) and the Moral Foundations Questionnaire (MFQ) were applied for a comparative evaluation of moral cognition across the two groups. The Positive and Negative Syndrome Scale (PANSS) was administered to assess the psychopathology. Results: SCZ had significantly greater CTQ than HCs (42.77±13.50 vs. 29.11±4.25, t=9.697, p<0.001). The prevalence of CT (χ2=58.452, p<0.001) and history of aggressive behaviors (χ2 =23.565, p=0.001) among SCZ were greater than that among HCs. In addition, the scores of moral cognition (MIM: 61.82±15.12 vs. 70.88±8.87, p=0.001; MFQ: 87.24±22.30 vs. 112.62±23.42, p=0.045) in the SCZ group was lower than that in the HC group after controlling for the influence of CT covariates. The MFQ score was negatively correlated with the CTQ, the emotional abuse (EA) score, the physical abuse (PA) score and the physical neglect (PN) score in SCZ. Among HCs, the MFQ score was positively correlated with the CTQ score, as well as with the dimensions of PA and EN. Multiple linear regression analyses revealed that impaired moral cognition performance was significantly predicted by the CTQ score (beta=-0.235, p=0.034, 95% CI -0.743 to -0.031) in SCZ but was significantly predicted by years of education (beta=-0.392, p＜0.001, 95% CI -4.783 to -1.876), alcohol use (beta=0.210, p=0.023, 95% CI 2.191 to 29.399) and the CTQ score (beta=0.184, p=0.046, 95% CI 0.019 to 1.928) in HCs. CTQ moderated the effect of SCZ on MFQ (B=0.516) ;Simple tests revealed that the group effect on the MFQ was B=12.306 at the lower level(-1SD) and B=54.089 at the higher level(+1SD) of the CTQ. Conclusions: SCZ exhibit impaired moral cognition. The contribution of CT to the presence of moral cognitive impairments seems to be independent of psychopathology.